2018
DOI: 10.1007/s10570-018-1832-1
|View full text |Cite
|
Sign up to set email alerts
|

In-situ analysis of polyelectrolyte complexes by flow cytometry

Abstract: Polyelectrolyte complexes (PECs) from common papermaking additives were prepared at different cation/anion ratios, resulting in colloidal light scattering particles. The polycations were cationic starches and polyDADMACs, while the polyanions were different carboxymethyl celluloses. The PECs were studied by turbidity measurements, as well as by flow cytometry (FCM). Turbidity maxima were detected close to the theoretical neutralization point of the polycation and polyanion. The turbidity response of the PEC mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Apoptosis is the programmed cell death that controls the development and homeostasis of multicellular organisms by elimination of aged, damaged or mutated cells, and which has been shown to be the key cellular event responsible for the anti‐cancer activity of metal anti‐cancer drugs . To determine whether the observed cell death induced by the three complexes was due to apoptosis, the interaction of HeLa cells with the complexes was investigated using an Annexin V‐FITC/PI assay.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis is the programmed cell death that controls the development and homeostasis of multicellular organisms by elimination of aged, damaged or mutated cells, and which has been shown to be the key cellular event responsible for the anti‐cancer activity of metal anti‐cancer drugs . To determine whether the observed cell death induced by the three complexes was due to apoptosis, the interaction of HeLa cells with the complexes was investigated using an Annexin V‐FITC/PI assay.…”
Section: Resultsmentioning
confidence: 99%
“…The shapes of the CNC populations were slightly different depending on the raw material used, which indicated that the choice of raw material influenced the resulting CNCs. Previously, FCM measurements of polyelectrolyte complexes (PECs) highlighted that the FSC and SSC offers quite different information about particles in suspension (Strand et al 2018). It was theorized that the SSC gives information about the amount of dense and light scattering surfaces in a particle, while the FSC offers information about the transparency of a particle, as well as the complexity of its external or internal texture.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium carboxymethyl cellulose, M w 250, degree of substitution 0.9, was obtained from Acros Organics. Polyelectrolyte complexes (PECs) were prepared from the cationic starch and CMCs at a polycation to polyanion ratio of 5.5:1 according to a previously published procedure (Strand et al 2018). The lipophilic extractives from thermomechanical pulp from Norway spruce were extracted with hexane.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations